Suburbanization in global society - Clapson, Mark; Hutchison, Ray (Research in urban sociology, 2010)
Most urban growth over the last several decades has been in suburban areas, but research in urban sociology and other urban disciplines has been focused on the city (the global city, the networked city, the post-industrial city). A majority of the world population lives in urban areas, most in suburban regions, including the shanty towns of Asia, favelas of South America, slums of Africa and banileue and inner-city suburbs of the developed nations. Suburbanization in Global Society presents new and innovative contributions in comparative suburban studies for urban regions, not just in Europe and the United States but also including emerging metropolitan regions in China, India and other areas of the world. This volume examines the emerging patterns of suburban development in metropolitan regions around the globe. Research is post-1945 with a particular focus upon social and cultural change in suburbanisation processes in developed as well as emerging urban countries.